Kiprah Pendidikan Pesantren di Indonesia Dalam Pespektif Filsafat Sejarah - Khairuddin (Hikmah, 2018)
The purpose of writing this article is to describe the progress of Islamic boarding schools in Indonesia from the perspective of historical philosophy. The writing method used is qualitative - descriptive. Based on the conceptual analysis it can be seen that the growth of Islamic boarding schools in Indonesia, there are four theories: First Islamic boarding schools established since the spread of Islam in Indonesia (Nusantara) in the 15th century AD, the first figure who founded was Syekh Maulana Malik Ibrahim proved that he developed his mission using mosques and Islamic boarding schools as trans-mission centers of Islamic science. Secondly, Islamic boarding schools began to emerge since the time of the Prophet, because at that time the Prophet's preaching was carried out clandestinely in a house like the house of one of the people named Arqom bin Abi Arqom. Third, Islamic boarding schools are the adoption of a model of Hinduism and Buddhism, when Islam grew and developed in Java. Fourth, Islamic boarding schools stand in the Dendenderi Islamic tradition, namely the tarekat tradition. Because this institution has a close relationship with the Sufi education model.